Yogis, Ayurveda, and Kayakalpa: The Rejuvenation of Pandit Malaviya - Newcombe, Suzanne (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
How should we read claims about health and well-being which defy common sense? Are claims of extreme longevity to be viewed as fraudulent, or as pushing the boundaries of possibility for the human body? This article will consider the narrative and context around a particularly well-publicized incident of rejuvenation therapy, advertised as kāyakalpa (body transformation or rejuvenation), from 1938. In this year, the prominent Congress Activist and co-founder of Banaras Hindu University, Madan Mohan Malaviya (1861–1946), underwent an extreme – and very public – rejuvenation treatment under the care of a sadhu using the name of Shriman Tapasviji (c.1770?-1955). The first half of the article will explore the presentation of Malaviya’s treatment and how it inspired a focus on rejuvenation therapy within Indian medicine in the years immediately following. Exploring this mid-twentieth century incident highlight some of the themes and concerns of the historical period, just out of living memory, but in many ways similar to our own.